MicroRNA-126 upregulation, induced by training, plays a role in controlling microcirculation in dexamethasone treated rats - Herrera, Naiara A. [UNESP]; Duchatsch, Francine [UNESP]; Tardelli, Lidieli P. [UNESP]; Dionísio, Thiago J.; Shinohara, Andre L.; Santos, Carlos F.; Amaral, Sandra Lia [UNESP] (Elsevier, 2020)
Microcirculation maintenance is associated with microRNAs. Nevertheless, the role of microRNAs induced by training in preventing dexamethasone (DEX)-induced microvascular rarefaction remains unknown. The study aim was to investigate if training-induced microRNAs are able to improve microcirculation proteins and prevent DEX-induced microvascular rarefaction. Rats underwent training for 8 weeks and then were treated with DEX (50 μg/kg per day, s.c.) for 14 days. Arterial pressure was measured and tibialis anterior (TA) muscle was collected for analyses. DEX induced hypertension concomitantly with capillary density loss (CD, −23.9%) and decrease of VEGF (−43.0%), p-AKT/AKT (−39.6%) and Bcl-2 (−23.0%) and an increase in caspase-3-cleaved protein level (+34.0%) in TA muscle. Training upregulated microRNA-126 expression (+13.1%), prevented VEGF (+61.4%), p-AKT/AKT (+37.7%), Bcl-2 (+7.7%) decrease and caspase-3-cleaved (−23.1%) increase associated with CD (+54.7%) reduction and hypertension prevention. MiRNA-126 upregulation, induced by training, plays a role in controlling microcirculation, which may be a potential target against DEX-induced microvascular rarefaction.
Keywords: Arterial pressure; Glucocorticoids; Microcirculation; Physical training; Skeletal muscle